Photosynthetic CO2 response to soil water and its simulation using different models in leaves of two species - Q. WU; T. ZHANG; C.R. LI; H.B. XIE; G.C. ZHANG (Photosynthetica, 2020)
CO2 concentrations and soil moisture conditions are important factors in photosynthesis of trees. This study investigated the photosynthetic CO2 responses in the leaves of Prunus sibirica L. and Pinus tabulaeformis Carr. under eight soil water conditions in a semiarid loess hilly region. CO2-response curves and physiological parameters were fitted using a rectangular hyperbola model, nonrectangular hyperbola model, exponential equation, and modified rectangular hyperbola model. Results revealed the relative soil water content (RWCs) for P. sibirica required to maintain higher photosynthetic rate ranging from 46.5 to 81.6%, and that for P. tabulaeformis ranging from 35.4 to 84.5%. When RWCs exceeded these ranges, the net photosynthetic rate of both species decreased. CO2-response curves and three parameters, carboxylation efficiency, CO2-compensation point, and photorespiration rate, were well fitted by the four models when RWCs was appropriate for P. sibirica and P. tabulaeformis. When RWCs exceeded the optimal ranges, only the modified rectangular hyperbola model could precisely simulate the CO2-response curves and photosynthetic parameters of both species.